Design of IoT-based System for Smart Temporary Waste Shelter - Muhammad Faza Izzaturrahman Nugroho; Istikmal Istikmal; Arif Indra Irawan (Jurnal Rekayasa Elektrika, 2021)
Internet of Things (IoT) is a concept where all products can interact with each other to help human activities by utilizing the internet. The IoT system can help solve problems such as the schedule-based retrieval system at a temporary shelter in Indonesia. This paper creates a web-based geographic information system along with the IoT-based waste temporary shelter prototype. The prototype also integrated with an Arduino Microcontroller so that it can sort the waste automatically into three types of waste, then record data in the form of height and weight, and send the results of the data to the database so that the geographic information system can display the results of the data. Node-RED serves as an Application Programming Interface (API) that sends data from the server to the database belonging to a web-based geographic information system. The results of the performance analysis are that the prototype has sorted waste well, and the system also produced good QoS by ETSI standards when looking at the network traffic from the MQTT server to the database, and from the end-user to the web. As for the QoE results for tools and systems have produced good results according to the ITU-T standard.